2011
DOI: 10.1037/a0024420
|View full text |Cite
|
Sign up to set email alerts
|

The family–study interface and academic outcomes: Testing a structural model.

Abstract: Expanding on family-work and work-study models, this article investigated a model for family-study conflict and family-study facilitation. The focus of the study was the relationship of family-study conflict and family-study facilitation with students' effortful behaviors and academic performance among a sample of university students (N = 1,656).. Model tests using structural equation modeling identified participation in family activities, family social support, and involvement with family as antecedents of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Meeuwisse, Severiens, and Born (2010) found that family-to-university conflict and facilitation were influenced by family involvement and support, and conflict (negatively) and facilitation (positively) were then related to effort. Others showed that core self-evaluations and proactive personality were antecedents to both work-university conflict and enrichment, and had direct and indirect effects (via conflict and facilitation) on university attendance, GPA, and satisfaction, and work performance and satisfaction, in the expected directions (McNall & Michel, 2011).…”
mentioning
confidence: 93%
“…Meeuwisse, Severiens, and Born (2010) found that family-to-university conflict and facilitation were influenced by family involvement and support, and conflict (negatively) and facilitation (positively) were then related to effort. Others showed that core self-evaluations and proactive personality were antecedents to both work-university conflict and enrichment, and had direct and indirect effects (via conflict and facilitation) on university attendance, GPA, and satisfaction, and work performance and satisfaction, in the expected directions (McNall & Michel, 2011).…”
mentioning
confidence: 93%
“…There is an increasing body of literature discussing the role of immigrant parents and the educational mobility of their children (See Crul and Doomernik, 2003;Keskiner, 2013;Louie, 2012;Meeuwisse, Born and Severiens, 2011;Portes and Fernández-Kelly, 2008). In the Netherlands when guest worker migrants abandoned their return plan to their country of origin and started to become aware of the relevance of educational credentials for achieving upward social mobility, they adjusted their ambitions for their children accordingly.…”
Section: Second Generation and Supportmentioning
confidence: 99%
“…We made use of the conceptual model of the family-study interface (Meeuwisse et al, 2011;Figure 1). In this model, the family-study interface is defined as the extent to which family life affects the ability of students to meet study- related demands and responsibilities in both a positive (i.e" facil itation) and a negative (i.e., conflict) way.…”
Section: Ethnic Differences In Interrole Conflict and Facilitationmentioning
confidence: 99%